Strategi Kehumasan Pemerintah Kota Tangerang dalam Mensosialisasikan Kegiatan Porprov VI Banten melalui Media Sosial - Meivia, Nanda Sheila; Delima, Isniyunisyafna Diah; Hardiyanti, Rini (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
As the times continue to develop, it is important for Public Relations officers to have new strategies to attract public attention and can include segmentation of local government activities. This study aims to determine the public relations strategy of the Tangerang City Government in disseminating Porprov VI Banten activities through social media. To explain this situation, researchers use qualitative methods. The results obtained were that the public relations strategy carried out by the Tangerang City Government Diskominfo was assessed by researchers as running according to the Cutlip, Center & Broom public relations strategy “7-CS Communication”. The communication activities they carried out in socializing governmental activities, such as Porprov VI Banten activities and information on other activities, were considered by researchers to be quite effective and efficient in attracting public interest to participate in Porprov VI Banten activities because they utilized various social media channels and packaged interesting information. To overcome obstacles in managing social media accounts owned by the Tangerang City Government, the Public Relations of the Tangerang City Government always coordinates with the team for the distribution of work.